Hacia la comprensión de factores comunes entre trastornos clínicamente distintos: Las intrusiones mentales en el espectro obsesivo-compulsivo. - Pascual-Vera, Belén; Ruiz, Mª Angeles; Belloch, Amparo (Revista de Psicopatología y Psicología Clínica, 2022)
Understanding common factors between clinically different disorders: Mental intrusions in the obsessivecompulsive spectrum Abstract: This study examines whether the propensity to experience obsessive, dysmorphic, hypochondriac and eating-related unwanted mental intrusions (UMIs) is a common vulnerability factor for these disorders. A total of 149 university students completed the Questionnaire of Unpleasant Intrusive Thoughts (QUIT) that assesses the frequency of and disturbance caused by the four UMI contents as well as self-reports of symptoms. 26.17% of participants experienced the four UMI contents during the past three months. The scores of each UMI were related to their specific self-report of symptoms and predicted the scores on these self-reports. Among those participants who experienced the four UMIs, 61.53% were at risk of obsessive-compulsive disorder (OCD). These subjects, compared to those who also experienced the four UMIs but were at low risk of OCD, reported more negative consequences when they experienced an UMI, regardless of its content. UMIs could be transdiagnostic and common vulnerability factors for different mental disorders. Keywords: Mental intrusions; transdiagnostic; obsessive-compulsive disorder; obsessive-compulsive spectrum. Resumen: Este estudio examina si la propensión a experimentar intrusiones mentales no deseadas (IM) con contenidos obsesivos, dismórficos, hipocondríacos y alimentarios es un factor común de vulnerabilidad para esos trastornos. Un total de 149 estudiantes universitarios completaron el Inventario de Pensamientos Intrusos Desagradables (INPIDES), que evalúa la frecuencia y el malestar con que se experimentan los cuatro contenidos de IM, junto con autoinformes de síntomas. El 26.17% había experimentado las cuatro IM en los tres meses previos. Las puntuaciones de cada IM correlacionaron con su autoinforme específico de síntomas y predijeron las puntuaciones en ellos. El 61.53% de quienes tuvieron las cuatro IM, presentó riesgo de trastorno obsesivo-compulsivo (TOC). Estas personas, comparadas con quienes también habían experimentado las cuatro IM pero tenían bajo riesgo de TOC, informaron de más consecuencias negativas cuando tenían una IM, independientemente de su contenido. Las IM podrían ser factores transdiagnósticos y de vulnerabilidad comunes a trastornos mentales distintos. Palabras clave: intrusiones mentales; transdiagnóstico; trastorno obsesivo-compulsivo; espectro obsesivo-compulsivo.